Dampak Penggunaan Gadget Terhadap Perilaku Anak Di Madrasah Ibtidaiyah Nurul Huda Lengkong Kecamatan Cerme Kabupaten Gresik - Rani Rahma Wati; Barudin (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2021)
Abstract: Students who study at MI Nurul Huda Lengkong 99% of children who study there already have personal gadgets and at home are already connected to a lot of internet or WIFI network services. With the focus of the problem: a. How is the use of gadgets for students of Madrasah Ibtidaiyah Nurul Huda Lengkong, Cerme District, Gresik Regency? b. What is the positive impact of using gadgets on the behavior of students of Madrasah Ibtidaiyah Nurul Huda Lengkong, Cerme District, Gresik Regency? c. What is the negative impact of using gadgets on the behavior of Madrasah Ibtidaiyah students Nurul Huda Lengkong, Cerme District, Gresik Regency? This study aims to determine the extent to which students of MI Nurul Huda Lengkong use gadgets, as well as the positive and negative impacts of using gadgets on the behavior of class V students. This type of research is qualitative with a descriptive approach, the types of data used are primary and secondary data. By using data collection techniques of observation, interviews and documentation. From the analysis of data collection, it can be concluded that the background of the use of gadgets for students at MI Nurul Huda is due to the busyness of parents working and the influence of the surrounding environment. So that the use of these gadgets has a more negative impact on children's behavior than the positive impact. The negative impact is that children spend more time playing gadgets, and it creates the effect of dependence on children to always play gadgets. And as for the positive impact on student behavior, children can add to their friendship through social media.